Impact of front line demonstration on performance of wheat (Triticum aestivum L.) in Muzaffarpur, Bihar - Mohammad Hashim; K. K. Singh; Shiva Dhar (Annals of Agricultural Research, 2022)
To bridge the yield gap between lab-to-land and to demonstrate production potential of improved technologies Front line demonstrations (FLDs) on wheat crop was conducted by ICAR- Indian Agricultural Research Institute, Regional Station Pusa, Samastipur Bihar during 2017-18 and 2018-19 in, different villages of Muzaffarpur, Bihar to know the yield gap, economic return, extent of farmer’s satisfaction and constraints faced by the farmers. Front line demonstrations (FLDs) were conducted on 16 farmers fields each year to demonstrate the impact of improved agro-techniques on production and economic benefits. HD 2967 variety was demonstrated with the use of bio-fertilizers- Azatobactor and PSB and zero-tillage technology. It was revealed that the demonstrated technologies under FLDs resulted in an augmented mean yield of 4.73 t/ha having an edge of 18.22% higher yield over Local Check (farmer’s practice) of 4.01 q/ha. Induction of demonstration technology recorded a mean technology gap (TG) of 1.79 t/ha, extension gap (EG) of 0.72 t/ha and technology index (TI) of 27.41 t/ha. The FLDs recorded an additional return of 18350.72 `/ha and 15221.25 `/ ha with B: C ratio of 1.44 and 1.58 for demonstration and 0.78 and 1.06 for Local Check during 2017-18 and 2018-19, respectively. Unavailability of improved high yielding varieties of wheat in relation to climate change was found to be most confronting constraint. Therefore, the wheat productivity could be increased with the adoption of new wheat varieties and recommended improved package of practices and technologies.